Seguridad de los antiinflamatorios no esteroideos - Oscanoa-Espinoza, Teodoro Julio (2015)
Abstract: The choice of a specific medication belonging to a drug class is under the criteria of efficacy, safety, cost and suitability. NSAIDs currently constitute one of the most consumed drug in the world, so it is very important review of the safety aspects of this drug class. This review has the objective of analyze the safety of NSAIDs on 3 main criteria: gastrolesivity, cardiotoxicity and nephrotoxicity.